2022
DOI: 10.3390/biomedicines10092267
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Patients with Brain Injury: Differences between Machine Learning versus Conventional Statistics

Abstract: Defining reliable tools for early prediction of outcome is the main target for physicians to guide care decisions in patients with brain injury. The application of machine learning (ML) is rapidly increasing in this field of study, but with a poor translation to clinical practice. This is basically dependent on the uncertainty about the advantages of this novel technique with respect to traditional approaches. In this review we address the main differences between ML techniques and traditional statistics (such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The only two patients for whom it was not feasible to establish the possible outcome had missing values at T1. The performance reported is in line with several previous studies using machine learning algorithms to predict outcomes in acquired brain injury 8 . In a previous study (Bruschetta et al 2022) different ML approaches were compared with the classic Linear Model (LM) to predict the final evolution of TBI patients according to 2 and 4 GOS classes based on the clinical assessment at T0.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The only two patients for whom it was not feasible to establish the possible outcome had missing values at T1. The performance reported is in line with several previous studies using machine learning algorithms to predict outcomes in acquired brain injury 8 . In a previous study (Bruschetta et al 2022) different ML approaches were compared with the classic Linear Model (LM) to predict the final evolution of TBI patients according to 2 and 4 GOS classes based on the clinical assessment at T0.…”
Section: Discussionsupporting
confidence: 90%
“…linear regression models) 7 . In fact, a recent narrative review showed that ML algorithms do not outperform traditional regression approaches for outcome prediction in brain injury 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The only two patients for whom it was not feasible to establish the possible outcome had missing values at T1. The reported performance is in line with several previous studies using machine learning algorithms to predict outcomes in acquired brain injury (Cerasa et al, 2022). In a previous study (Bruschetta et al, 2022) different ML approaches were compared with the classic Linear Model (LM) to predict the nal evolution of TBI patients according to 2 and 4 GOS classes based on the clinical assessment at T0.…”
Section: Discussionsupporting
confidence: 84%
“…This is basically dependent on the uncertainty about the intrinsically ''black-box'' nature of this approach and the lack of clear advantages with respect to traditional approaches (i.e linear regression models) (Quinn et al, 2022). Indeed, a recent narrative review showed that ML algorithms do not outperform traditional regression approaches for outcome prediction in brain injury (Cerasa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation